PENGARUH RETURN ON ASSET (ROA) DAN CURRENT RATIO (CR) TERHADAP HARGA SAHAM PADA PT WIJAYA KARYA (PERSERO) TBK PERIODE 2013 – 2023 - Hasanah, Fitri; Gunawan, Hendri (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Return On Assets (ROA) and Current Ratio (CR) on share prices both partially and simultaneously at PT Wijaya Karya (Persero) Tbk. The research method used is a quantitative method. The population in this research is all of the Financial Reports of PT Wijaya Karya (Persero) Tbk. The sample used in this research is the financial position report and profit and loss report from 2013 - 2023. The data analysis techniques used are Descriptive Analysis, Classical Assumption Test, Coefficient of Determination Test, Multiple Linear Regression Analysis, and Hypothesis Testing. The results of this research show that the calculated t value of Return On Assets is -1.238 which is smaller than the t table value of 2.306 (-1.238 < 2.306) with a significance value of 0.0251 which is greater than 0.05 (0.0251 > 0.05). So it can be concluded that Return On Assets does not have a significant influence on share prices. Meanwhile, the calculated t value of the Current Ratio is 6.142 which is greater than the t table value of 2.306 (6.142 > 2.306) and the significant result of the Current Ratio is 0.001 which is smaller than 0.05. So it can be concluded that the Current Ratio has a significant effect on share prices. Then the Return On Asset and Current Ratio simultaneously have a significant influence on the share price at PT Wijaya Karya (Persero) Tbk for the 2013 - 2023 period as evidenced by the calculated F of 24.009 which is greater than the F table of 4.26 (24.009 > 4.26) and the value significant of (0.001 < 0.05).